2011
DOI: 10.1007/s10209-011-0233-0
|View full text |Cite
|
Sign up to set email alerts
|

Designing for collaboration: a study in intergenerational social game design

Abstract: This paper presents a study of a computer game designed for the elderly, allowing them to train their memory while playing the game. The game supports both a single-player and a multiplayer mode, in which the elderly can play with their friends or family using an embedded video chat application. The main question that is addressed in this paper is how the elderly gamers' experience is influenced by the possibility to communicate directly with the other players. The study presents a comparison of the game exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…Intergenerational digital gameplay creates a natural context for common goals, cooperation, and equal status that are key factors for intergenerational interaction (Chua et al, 2013). Zhang and Kaufman's (2016a) review study identified 11 digital games developed to facilitate intergenerational interaction and learning, such as Distributed Hide-and-Seek (Vetere, Nolan, & Raman, 2006), Curball (Kern, Stringer, Fitzpatrick, & Schmidt, 2006), TranseCare (Derboven, Van Gils, & De Grooff, 2011), Age Invaders (Khoo, Cheok, Nguyen, & Pan, 2008), etc. Digital games can transcend the dimensions of time, space, and close personal relationships and allow players to practice intergenerational skills in a safe environment (Ypsilanti et al, 2014).…”
Section: Intergenerational Digital Gameplaymentioning
confidence: 99%
“…Intergenerational digital gameplay creates a natural context for common goals, cooperation, and equal status that are key factors for intergenerational interaction (Chua et al, 2013). Zhang and Kaufman's (2016a) review study identified 11 digital games developed to facilitate intergenerational interaction and learning, such as Distributed Hide-and-Seek (Vetere, Nolan, & Raman, 2006), Curball (Kern, Stringer, Fitzpatrick, & Schmidt, 2006), TranseCare (Derboven, Van Gils, & De Grooff, 2011), Age Invaders (Khoo, Cheok, Nguyen, & Pan, 2008), etc. Digital games can transcend the dimensions of time, space, and close personal relationships and allow players to practice intergenerational skills in a safe environment (Ypsilanti et al, 2014).…”
Section: Intergenerational Digital Gameplaymentioning
confidence: 99%
“…An intergenerational game (IGG) is a game that provides an inclusive and shared entertainment experience that is appealing across developmental ages from children to adults, representing a common ''meeting ground'' for families. [35][36][37][38] In an IGG both parents and youth can play an active role in winning the game, in contrast to parental monitoring of child-led gaming activities. Health-related IGGs, therefore, could bridge the ''communication gap'' to induce interaction between parents and their youth as a mediator to positively impact health behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Digital games can also have a mutual value for both generations by encouraging communication, solidarity, and social connectedness between generations (Al Mahmud, Mubin, Shahid, & Martens, 2010;Derboven et al, 2012), tear down some stereotypes, and probably reduce the gap between generations and the disparities in authority of (grand) child-(grand) parents' relationships (Mesch, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…For older adults, they can improve cognitive functioning (e.g., short-term capacity, attention, handeye coordination) (Whitlock, McLaughlin, & Allaire, 2012); overcome communication problems and social isolation; and encourage physical exercising and prevent falls (Derboven, Van Gils, & De Grooff, 2012;De Schutter & Vanden Abeele, 2008).…”
Section: Introductionmentioning
confidence: 99%